The Holiness of Doubt: A Journey Through the Questions of the Torah - Hoffman, Joshua (Rowman & Littlefield Publishers, 2023)
The Holiness of Doubt is a timely and essential contribution to the study of sacred Jewish texts. What does it mean for a book of faith for millions of people to be riddled with the uncertainties evoked by hundreds of questions? Rabbi Joshua Hoffman has chronicled the questions of the Torah and offers personal insights and the accumulated wisdom of interpretations, ancient and modern, to discover the meaning of questions and the holiness of doubt. This book offers the reader a chance to see the wisdom of the Torah refracted through its questions. Divided according to the weekly Torah portions as traditionally studied in the Jewish community, this book explores the purpose of questions in the text and becomes a unique interpretation of the Torah on its own. There are also summaries for the portions which do not contain questions to explore what impact the absence of questions has on the Torah as a whole. In confronting doubt, we gain a renewed permission to explore the deepest questions of our time. We can discover, like our ancestors dreamed, that the wisdom of the biblical tradition echoes eternal truth in every generation.